(untitled) (Eurasian Research Bulletin, 2023)
This study aimed to assessment of some microbiological and physicochemical properties of local cheese as the addition of olive leaf extract influenced them. The most abundant components in olive leaf based on gas chromatography-mass spectrometry analysis were methyl alpha-D-mannoside, tetradecanoic acid, oleic acid, 3 alphaacetoxy-25-ydroxy-olean-12-en-28-oic acid, and carbamic acid. Powdered olive leaf extract was added to the cheese at concentrations of 10%, 20%, . The chemical and microbiological properties of the cheese were then determined at storage times of 0, 8, and 19 days at 4°C. The results showed that raising the percentage of olive leaf extract lowered the titratable acidity of the cheese. However, when the pH level rose, so did the few dried olive leaves added. Total plate counts in the cheese samples of the treated groups were lower (p <0.05) than in the untreated groups throughout the refrigerated storage. Olive leaves at the level of 20 % were more effective in inhibiting bacterial growth than 10 %. According to the findings of this study, extracts of olive leaves have the potential to be used to extend the shelf life of food products and can be used as a natural preservative>